Dis/locating Preferential Memory within Settler Colonial Landscapes: A Forward-Looking Backward Glance at Memoration’s Per/formation - Decter, Leah (Performance Matters)

(untitled) (Institute for Performance Studies, Simon Fraser University, 2021)
The degree to which authorized sites of commemoration such as monuments perpetuate deep-rooted practices of selective remembering and forgetting in settler states, and in doing so, help to entrench narratives and mythologies that mask ongoing colonial occupation and violence while denying Indigenous sovereignty, has arguably never been more evident. While official sites of remembrance undoubtedly shape the dominant imaginary, vernacular forms of commemoration exerted implicitly and explicitly in everyday life are also powerfully influential in the circulation of the nation’s ascendant ideation as what Audra Simpson calls “narration[s] of truth.” This paper will examine the ways “memoration,” an artistic/performance methodology I have developed through my inter-media art practice and scholarship, performs interventions into commemoration in the guise of public, national, and personal memory. As an adaptable and inherently relational, embodied and place-based methodology, memoration offers a framework of in Andrew Herscher's terms, “remembering otherwise”: one that activates a reckoning with the intergenerational responsibilities of being-in-relation, in my case as a white settler, on Indigenous lands that are at the same time “occupied” and unceded.